Returning from Iran - Geller, A; Latek, M (Refugee Studies Centre, University of Oxford, 2014)
Understanding the factors that have an impact on refugee decision making about return and people’s ability to reintegrate following return is critical in planning appropriate pre- and post-return programmes for Afghan refugees in Iran